Capa Física y de Enlace de la Tecnología PLC - García Guibout, J. (2007)
PLC technology1 - Power Line Communications- refers to the transmission of data using the domestic as well as the low-voltage electrical net. Depending on the type of network used as support it is divided in PLC indoor and outdoor. The first refers to the use of the domestic network and uses higher frequencies (5 MHz to 30 or 40 MHz). Outdoor PLC uses the distribution network and low frequencies of 1 MHz to 5 or 10 MHz. It employs the OFDM multiplexation technique- Orthogonal Frequency Division Multiplexing- which divides the frequency spectrum in narrow channels with independent carriers. At the level of media access protocol, it generally uses those which are compatible with the IEEE 802 norm, with controlled access to avoid collisions. OFDM modulation achieves transmission speeds which are suitable for multimedia services and applications as well as those of critical mission currently used, and with security conditions when facing a noisy channel such as the power network.